Fluoroquinolone resistance in clinical isolates of Streptococcus pneumoniae from Asian countries: ANSORP study - Oh, W.S.; Suh, J.Y.; Song, J.H.; Ko, K.S.; Jung, S.I.; Peck, K.R.; Lee, N.Y.; Yang, Y.H.; Chongthaleong, A.; Chiu, C.H.; Kamarulzaman, Adeeba; Parasakthi, N.; et al. (Mary Ann Liebert, 2004)
Seventeen clinical isolates of Streptococcus pneumoniae showing reduced susceptibility to ciprofloxacin (MIC : 4 mug/ml) collected from eight different Asian countries were analyzed by antimicrobial susceptibility, serotyping, pulsed-field gel electrophoresis (PFGE), and DNA sequencing of the quinolone resistance-determining regions (QRDRs) in gyrA, gyrB, parC, and parE. All isolates but one showed more than one amino acid alteration in QRDRs of four responsible genes. Ile460 —> Val in parE was the most common mutation. Data suggest that Lys137 —> Asn in parC may be a primary step in the development of high-level and multiple FQ resistance. An additional mutation of Ser81 —> Phe in gyrA resulted in high-level resistance to ciprofloxacin, levofloxacin, and gatifloxacin, whereas Ser79 —> Phe in parC may exert an important role in the development of moxifloxacin resistance. Two novel amino acid changes in gyrB, Ala390 —> Val and Asn423 —> Thr, were found. Data from PFGE suggest an introduction and local spread of multiple resistant Spain(23)F-1 clone in Hong Kong, but isolates from other Asian countries were not related to this clone.